2016
DOI: 10.1007/s11092-016-9255-8
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of Japanese middle school student and school socioeconomic status influence on mathematics achievement

Abstract: The results indicated that at the student level, different aspects of student SES (i.e. number of books, the possession of computers, paternal, and maternal educational achievements were positively related to Japanese student math achievement. At the school level, two aspects of school SES (i.e. less populated schools and economically disadvantaged schools) were negatively related to Japanese student math achievement.Especially, Japanese students who attended schools in less populated areas were more disadvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…This indicates that if the learning support at home is fulfilled properly, it will ease students to do learning activities, in order to improve student learning achievement. The findings are the same as the results of previous studies which state that the learning support at home has a significant effect on improving student learning achievement (Liu et al, 2006;Takashiro, 2017;Yoshino, 2012).Thus, the learning support or usually known as learning facilities are better fulfilled by parents so that students obtain better result.…”
Section:  Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This indicates that if the learning support at home is fulfilled properly, it will ease students to do learning activities, in order to improve student learning achievement. The findings are the same as the results of previous studies which state that the learning support at home has a significant effect on improving student learning achievement (Liu et al, 2006;Takashiro, 2017;Yoshino, 2012).Thus, the learning support or usually known as learning facilities are better fulfilled by parents so that students obtain better result.…”
Section:  Results and Discussionsupporting
confidence: 88%
“…Rich parents in most cases spend money on students' learning resources such as books, educational games, laptops and also on extracurricular courses (Koza Çiftçi & Cin, 2017;Sirin, 2005). Students who has more learning supports (such as book and computer) tend to have more benefits than others (Takashiro, 2017). This finding is consistent with Japanese International research revealing that the level of mathematics achievement is influenced by socioeconomic status across their schools.…”
Section:  Results and Discussionsupporting
confidence: 66%
“…The Trends in International Mathematics and Science Study (TIMSS) provides information on SES indicators related to student achievement including the parental education level, the number of books at home, and home educational resources. TIMSS data over time has consistently shown positive effects between student achievement and SES indicators (see Baker et al 2002;Bouhlila 2015;Byun and Kim 2010;Chudgar and Luschei 2009;Hanushek and Luque 2003;Harris 2007;Liu et al 2006;Takashiro 2016;Yang 2003). For example, Baker et al (2002) explored both the effect of student SES and school resource quality on student achievement in 36 countries, finding parent education levels and the number of books at home as important.…”
Section: Socio-economic Status and Student Performancementioning
confidence: 99%
“…Going to a high SES school may confer protective benefits that could reduce inequality’s harmful consequences. Studies have found that high-SES schools with a higher number of middle-class families have positive school climates that benefit students (Coleman, 1966; Takashiro, 2017). The positive benefits are especially pronounced for students who come from more disadvantaged families.…”
Section: Discussionmentioning
confidence: 99%
“…School SES could weaken the negative association between income inequality and school belonging. This hypothesis is based on several past studies showing the protective function of studying in higher SES schools (Coleman, 1966;Takashiro, 2017;Willms, 1999). Hence, we posit the following hypothesis: H2: School SES will moderate the effects of income inequality on school belonging.…”
Section: The Present Studymentioning
confidence: 99%